2008
DOI: 10.1007/s00441-008-0721-6
|View full text |Cite
|
Sign up to set email alerts
|

PBAN/pyrokinin peptides in the central nervous system of the fire ant, Solenopsis invicta

Abstract: The pyrokinin/pheromone-biosynthesis-activating neuropeptide (PBAN) family of peptides found in insects is characterized by a 5-amino-acid C-terminal sequence, FXPRLamide. The pentapeptide is the active core required for diverse physiological functions, including the stimulation of pheromone biosynthesis in female moths, muscle contraction, induction of embryonic diapause, melanization, acceleration of puparium formation, and termination of pupal diapause. We have used immunocytochemical techniques to demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…This absence raised questions about possible compensation of functions of CAPA peptides. In previous studies on S. invicta [5], [30], distinct PK/PBAN immunoreactivity was observed in abdominal ganglia and associated PSOs. However, pk/pban -mRNA transcription was not detectable in these tissues (see also Fig.…”
Section: Discussionmentioning
confidence: 73%
“…This absence raised questions about possible compensation of functions of CAPA peptides. In previous studies on S. invicta [5], [30], distinct PK/PBAN immunoreactivity was observed in abdominal ganglia and associated PSOs. However, pk/pban -mRNA transcription was not detectable in these tissues (see also Fig.…”
Section: Discussionmentioning
confidence: 73%
“…A similar two gene expression pattern for PK/PBAN-like peptides has been proposed for Solenopsis sp. (Choi et al 2009), Manduca sexta (Loi and Tublitz 2004), Bombyx mori (Roller et al 2008), and Periplaneta americana (Predel and Eckert 2000;Schoofs et al 1992). A search of the Anopholes gambiae genome indicates that these same two genes putatively code for peptides in the PK/PBAN family (Riehle et al 2002) The PKs produced by capa and hugin have been confirmed by mass spectroscopy in the mosquito A. aegypti (Predel et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…In different insect species including social insects several neuropeptides had been detected in the SEG, such as FMRFamide-like peptides, FXPLRamide related peptides (e.g. PBAN), neuropeptide F (NPF) and short neuropeptide F (sNPF) [33], [57], [58]. The expression pattern of the sNPFR in the SEG varies slightly among worker subcastes as shown under results (Figure 6), however, dramatic differences were observed in the SEG when comparing workers from colonies with and without brood (Figure 8).…”
Section: Discussionmentioning
confidence: 99%